HUBUNGAN ANTARA SELF-REGULATED LEARNING DENGAN KEMATANGAN KARIR SISWA KELAS XI DI SMKN 5 MATARAM - Tania Aristantia Taniar; Eneng Garnika; M. Zainal Mustamiin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Self-regulated learning refers to students’ ability to manage their learning process systematically and continuously, encompassing the stages of planning, implementation, and evaluation of their own learning outcomes. Meanwhile, career maturity is defined as students’ readiness to plan their careers, explore and gather career-related information, and make appropriate and responsible career decisions. Students with a high level of self-regulated learning tend to be more capable of derecting themselves in planning and making independent career decisions. This study aimed to exanime the relationship between self-regulated learning and career maturity among eleventh-grade students as SMK Negeri 5 Mataram in the 2025/2026 academic year. This research amployed a quantitative approach with a correlational research design. The population consisted of 334 eleventh-grade students, and a sample of 77 students was selected for the study. Data were collected using a Likert-scale questionnaeri as the primary instrument, while observation, interviews, and documentation were employed as supporting data collection methods. The data were analyzed using the pearson product-moment correlation technique. The findings revealed a correlation coefficient of 0,660 with a significance value of 0,000. since the significance value was lower than 0,05, the null hypothesis (H0) was rejected and the alternative hypothesis (Ha) was accepted. Therefore, the findings indicate a positive and significant relationship between self-regulated learning and career maturity among eleventh-grade students at SMK Negeri 5 Mataram in the 2025/2026 academic year.